Mentorship needs of early career teachers working in rural regions - Kartal, Secil Eda; Ozdemir, Tuncay Yavuz; Yirci, Ramazan (Mehmet Tekerek, 2017)
The purpose of this study is to identify the problems that teachers working in rural regions encounter concerning the Turkish educational system during the years they lack knowledge and experience and to determine their needs for mentorship services. The data was collected through an interview form and 11 teachers who works in rural regions participated into the research voluntarily. The study group was defined using purposeful sampling method. The data were analyzed through the content analysis processes. According to the findings of the study; teachers working in rural regions encounter serious problems in time management during the early years of their profession and that the effectiveness of presenting teaching contents decrease due to lack of family participation, low level of student academic achievement, poor physical conditions of the school and insufficient amount of teaching materials. It was also observed that they had problems in administrative issues and official correspondence. Arranging effective in-service training activities and offering mentorship services for inexperienced teachers in rural regions may help to resolve these problems.
Keywords: Teacher training; mentoring; teacher qualifications; professional development; mentoring needs